A simple and cost-effective approach to fabricate tunable length polymeric microneedle patches for controllable transdermal drug delivery. Issue 26 (20th April 2020) - Chen, Yongli; Xian, Yiwen; Carrier, Andrew J.; Youden, Brian; Servos, Mark; Cui, Shufen; Luan, Tiangang; Lin, Sujing; Zhang, Xu
Abstract : A simple and cost-effective approach to fabricate tunable length polymeric microneedle patches for controllable transdermal drug delivery. Abstract : Polymeric microneedles (MNs) are attractive transdermal drug delivery systems because of their efficient drug delivery and minimal invasiveness. Master template fabrication is the most time-consuming and costly step in producing polymeric MNs using a micromoulding approach. Herein, this issue is addressed by modifying tattoo needle cartridges by adjusting the volume of a PDMS spacer, thus streamlining polymeric MN fabrication and significantly reducing its manufacturing cost. Using the fabricated master template, dissolvable polymeric MN systems containing poly(vinyl pyrrolidone) (PVP) and poly(vinyl alcohol) (PVA) were developed. This MN system exhibits several advantages, including controllable MN length, uniform distribution of each needle, and controllable drug release profiles. Overall, polymeric MN fabrication using this method is inexpensive, simple, and yields controllable and effective transdermal drug delivery.